Learning about the unknown: How fast do entrepreneurs adjust their beliefs? - Parker, Simon C. (Journal of Business Venturing, 2006)
This paper seeks to measure the extent to which entrepreneurs adjust their beliefs in the light of new information, instead of relying on past experience to guide their decision making. We build a model in which entrepreneurs continually receive valuable but noisy market signals about the true but unobserved productivity of their effort, and use this information to update their expectations of unobserved productivity. The model is estimated using a sample of over 700 self-employed Britons interviewed in 1999 and 2000. It is found that on average, these individuals adjust their expectations of unobserved productivity in the light of new information by only 16%. This suggests that while entrepreneurs do exploit new information, they give much greater weight to their prior beliefs when forming their expectations. Also, there are no significant differences in terms of expectation formation between males and females, employers and non-employers, and experienced and less experienced entrepreneurs. However, younger entrepreneurs respond significantly more sensitively to new information than older entrepreneurs do, with adjustment rates of 21% compared with 14%, respectively. We go on to discuss some policy implications of these findings, and briefly discuss several features of entrepreneurship education programs that might help entrepreneurs improve this aspect of their business performance.